Traumatic intradiploic epidermoid cyst manifest as scalp papule. (16th February 2015) - Dupre, Derrick Andrew; Pu, Cunfeng; Yu, Alex; Tomycz, Nestor
Abstract : A posterior fossa intradiploic epidermoid cyst was removed from the calvarium of an otherwise healthy 34-year-old woman after work up for dizziness and blurry vision. The patient admitted to a history of a firm papule that occurred occasionally after a trauma sustained to the region years prior. The authors propose that trauma and cutaneous stigmata are potential associations with intradiploic epidermoid cysts.